2015
DOI: 10.1155/2015/196495
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association between Methylenetetrahydrofolate Reductase Gene Polymorphism and Risk of Osteonecrosis of the Femoral Head

Abstract: Background. Methylenetetrahydrofolate reductase (MTHFR) SNP rs1801133 has been frequently investigated in recent years. Relevant candidate gene association studies with this SNP and osteonecrosis of the femoral head (ONFH) reported conflicting results. Meta-analysis provides a method to combine these data and to determine the association in a larger sample size. Method. We conducted a systematic search to identify possible studies. Four pooled ORs (odds ratios, T versus C, TT versus CC, TT/CT versus CC, and TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
1
12
1
Order By: Relevance
“…When ethnicity was strati ed, this meta-analysis provided no evidence of an association between rs1801133 polymorphism and ONFH. Twelve studies were included in the meta-analysis of Chai et al (2015). The results showed that there was no direct association between ONFH susceptibility and rs1801133 polymorphism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When ethnicity was strati ed, this meta-analysis provided no evidence of an association between rs1801133 polymorphism and ONFH. Twelve studies were included in the meta-analysis of Chai et al (2015). The results showed that there was no direct association between ONFH susceptibility and rs1801133 polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis SPSS 24.0 (SPSS, Chicago, IL) was used for statistical analysis. The allele distribution was tested for Hardy-Weinberg equilibrium (HWE) by χ 2 . The ORs and 95% CI was determined by unconditional logistic regression analysis.…”
Section: Dna Methylation Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…With advancements in molecular techniques, genetic factors have been generally accepted to play critical roles in the etiology of non-trauma ONFH [8]. A variety of genes have been confirmed to be involved in ONFH pathogenesis, such as MTHFR, CYP3A4, CYP2D6, CYP2C19, ABCB1/MDR1, and nitric oxide synthase 3 (NOS3) gene [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The polymorphisms of multiple genes have been suggested to be associated with ONFH risk. These polymorphisms are thought to cause disequilibrium with other genes, affecting ONFH occurrence, or to play a synergistic role in the development of ONFH by interfering with the expression of other genes (3)(4)(5)(6) The ONFH patients often occur with a severe lipid metabolism disorder and the adipose accumulation in the impaired bone marrow cavity. Thus, lipid metabolism disorder has generally been regarded as a critical factor in ONFH pathogenesis, but the molecular mechanism of the adipose accumulation remains unclear.…”
Section: Introductionmentioning
confidence: 99%